Review Deskriptif: Psikologi Kepribadian dengan Pendekatan Eksistensial, Trait (Sifat), Teori Medan, Faktorial, Stimulus Respon (SR), dan Biobudaya Religius Karya: Ki Fudyartanta - Euis Ismaliawati; Yusi Riksa Yustiana (Indonesian Journal of Educational Counseling, 2026)
This article presents a descriptive critical review of Ki Fudyartanta’s book Personality Psychology: Various Approaches, which maps a wide range of theoretical perspectives used to understand the structure, dynamics, and development of human personality. The book discusses six major approaches, namely the existential approach, the trait approach, field theory, the factorial approach, the stimulus response S R approach, and the biocultural religious approach. This review outlines the core concepts of each approach and highlights their contributions to explaining the psychophysical uniqueness of individuals. In addition to presenting Western theories that are empirical and mechanistic, Fudyartanta introduces an integrative biocultural religious framework that positions spirituality, cultural values, and moral orientation as fundamental components in shaping the personality of Indonesian individuals. The analysis demonstrates that understanding personality requires a multidimensional and contextual perspective that integrates biological, psychological, social, and religious dimensions to portray humans holistically